Traces of Honeybees, Api-Tourism and Beekeeping: From Past to Present - Erkan Topal (MDPI AG, 2021)
Throughout history, honey has been used for many different purposes and due to its medicinal properties, has been one of the products marketed by traders. The figure of the bee first appeared in drawings on rock with the history of humanity, then on statues, as a logo, on money or stamps, and also in movies. Beekeeping museums, which present the historical process of beekeeping, also reflect an important culture with their ancient hives, documents, beekeeping materials, and historical antiquities. The contribution of bees to the sustainability of natural life is very important and has a history of 100 million years. The importance of bees and their by-products is increasing day by day, and the demand for the beekeeping industry as alternative income determines the emergence of new products and activities. Based on its health properties, apitherapy is the basis of activities such as api-air and api-diet. In natural regions (i.e., mountainous areas, forests) where beekeeping is carried out, people’s tradition, food culture, and healthy lifestyle attract society’s attention. In this context, api-tourist activity appears as a new phenomenon. In this article, the existing literature was scanned to create a resource about these new fields triggered by the beekeeping sector.